2017
DOI: 10.1016/j.mjafi.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of injuries and Road Traffic Accidents amongst service personnel in a large Defence station

Abstract: Age-specific Behavioural Change Communication strategies aimed at refining user outlook are imperative; tailored to sociodemographic milieu of user/victim. Incorporation of a dynamic feedback/reporting mechanism, creation of 'armed forces-specific road safety and injury prevention policy' and safety audits on injuries and road crashes are measures in this direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
1
4
0
1
Order By: Relevance
“…In total, 91.0% of those involved in accidents belong to the active workingage group, while the remaining 9.0% consisted of the young and aged group. Montazeri [29} and Neelakantan et al, [30] reported a similar finding in their studies.…”
Section: Gender Involvement In Accidentssupporting
confidence: 70%
See 1 more Smart Citation
“…In total, 91.0% of those involved in accidents belong to the active workingage group, while the remaining 9.0% consisted of the young and aged group. Montazeri [29} and Neelakantan et al, [30] reported a similar finding in their studies.…”
Section: Gender Involvement In Accidentssupporting
confidence: 70%
“…Osun State is an inland state in south-western Nigeria, located within latitude 7°30'N, longitude 4°30'E and latitude 7.5°N longitude 4.5°E. The state covers a total landmass of about 9,251 km 2 (3,572 square miles) and consists of thirty (30) local government areas, one (1) Area Office (Modakeke) and more than 200 towns. The 2006 national census reported a population of 3,416,959 for the state.…”
Section: The Study Areamentioning
confidence: 99%
“…Human factor was a significant determinant in road traffic accidents (RTAs) and injuries. A majority of victims admitted that human factors were the predominant cause of road accidents; and opined that the events were preventable 2 …”
Section: Discussionmentioning
confidence: 99%
“…Road traffic collision is generally classified as a human-induced disaster, which is on a very rapid increase, complex, and influenced by multidimensional factors [9,10]. Amongst all identified determinants and factors of RTC, human behaviours or actions appear to be the predominant factors [11]. About 90% of RTC cases and injuries occur in developing countries, and 12 countries in sub-Saharan Africa are listed in the top 20 RTC-prone countries for cases and casualties [12].…”
Section: Introductionmentioning
confidence: 99%